Dynamics of severity of coffee leaf rust (Hemileia vastatrix) on Coffee, in Chanchamayo (Junin-Peru) = Dinámica de la severidad de la roya (Hemileia vastatrix) en café, en Chanchamayo (Junín-Perú) - Alvarado Huamán, Leonel Eduardo
Introduction. Coffee (Coffea arabica L.) is an important crop in producing countries like Peru, where approximately two million families depend on its production, distribution, and marketing. But in recent years, climate change has increased the presence of coffee leaf rust - CLR (H. vastatrix), a disease that has decreased Peruvian production by up to 27%. Objective. Monitor the severity of CLR in different genotypes of coffee cv. Typica from April-2017 to March-2018. Material and methods. The experiment was carried out in the coffee germplasm bank at the Development Regional Institute (IRD)-Selva of the Universidad Nacional Agraria La Molina. The severity and the area under the disease progress curve (AUDPC) in the lower, middle, and upper part of coffee trees were quantified. Result. There was high severity and AUDPC in the dry season (low precipitation) compared to the rainy season (high precipitation). Severity and AUDPC gradually decreased from the bottom to the top of the plant (lower>middle>upper). Also, UNACAF-24A, UNACAF-16, UNACAF-158, and UNACAF-162 genotypes stood out by showing lowest severity (0-1.1 %) and AUDPC (0-714) in the experiment. Conclusion. In this experiment, the genotypes in dry season presented high peaks of severity and UDPC of CLR, meanwhile, in rainy season the presence of CLR was lower. However, in both seasons, severity and AUDPC gradually decreased from the lower third to the upper thirf of the plant. Finally, UNACAF-24A, UNACAF-16, UNACAF-158, and UNACAF-162 presented the lowest degrees of severity of CLR.